Green Synthesis of Luminescent Gold-Zinc Oxide Nanocomposites: Cell Imaging and Visible Light–Induced Dye Degradation - Bharti, Kanika; Lone, Shahbaz Ahmad; Singh, Ankita; Nathani, Sandip; Roy, Partha; Sadhu, Kalyan K. (Frontiers in Chemistry, 2021)
Green synthesis of gold-zinc oxide (Au-ZnO) nanocomposite was successfully attempted under organic solvent–free conditions at room temperature. Prolonged stirring of the reaction mixture introduced crystallinity in the ZnO phase of Au-ZnO nanocomposites. Luminescence properties were observed in these crystalline Au-ZnO nanocomposites due to in situ embedding of gold nanoparticles (AuNP) of 5–6 nm diameter on the surface. This efficient strategy involved the reduction of Au(III) by Zn(0) powder in aqueous medium, where sodium citrate (NaCt) was the stabilizing agent. Reaction time and variation of reagent concentrations were investigated to control the Au:Zn ratio within the nanocomposites. The reaction with the least amount of NaCt for a long duration resulted in Au-ZnO/Zn(OH)2 nanocomposite. X-ray photoelectron spectroscopy (XPS) confirmed the formation of Zn(OH)2 and ZnO in the same nanocomposite. These nanocomposites were reconnoitered as bioimaging materials in human cells and applied for visible light–induced photodegradation of rhodamine-B dye.